To what extent does governance affect funding of non-government organisations in Mauritius? - Pillai, Savishna (Department of Social Development, 2015)
This research study To what extent does governance affect funding of non-governmental organisations in Mauritius? was conducted in year 2013 and 2014. It sought to investigate how good governance practices had increasingly become a prerequisite in the service delivery of Non-Governmental Organisations (NGOs) in the country. Mauritius is often referred as the ‘Star’ of the Indian Ocean due to its successful socioeconomic development, rapid growth in its standard of living and the consolidation of its democratic institutions. However, the country, without any natural resources and heavily dependent on its multi ethnic population, remained among the most vulnerable countries in the world to global economic changes. In recent years the number of NGOs had mushroomed around the island to bring unprecedented contributions to grassroots communities’ development. This had raised the need to address the importance and impact NGOs have had on policies and in advancing initiatives that used to be exclusively in the domain of the State and Private Sector. With increased importance, came increased responsibility. The State aimed for NGOs to develop a system of proper governance. The rationale of this study was based on the premise that many NGOs in Mauritius were not aware of the characteristics of good governance practices. In addition, it explored the correlation between good governance and funding. Studies on governance of NGOs worldwide, demonstrated that most of them were facing funding issues due to failure in applying good governance practices. Also, among the main objectives of the research study were to identify between good and bad governance practices which affected the administration of NGOs.